Spectroscopic and electrochemical behavior of the novel tetra-2-methyl-pyrazinoporphyrazines - Piskin, Mehmet; Ozturk, Naciye; Durmuş, Mahmut (Elsevier Science Bv, 2017)
This study presents the synthesis and characterization of novel metal-free (H2Pc) and metallo porphyrazines (magnesium(II) (MgPz), copper(II) (CuPz), iron(II) (FePz), manganese(II) (MnPz) and nickel(II) (NiPz)) substituted with four 2-methylpyrazine groups on the peripheral positions. The spectroscopic properties of newly synthesized porphyrazines were investigated. The electrochemical behaviors of these porphyrazines were also determined in DMSO solution by cyclic voltammetry (CV) and square wave voltammetry (SWV) methods on edge plane pyrolytic graphite electrode (EPPG) electrode. (C) 2017 Published by Elsevier B.V.
Keywords: Porphyrazine; 2-Methylpyrazine; Electrochemistry; Cyclic voltammetry